THE DETERMINATION OF THE CURRENT CHANGE RATE IN THE CIRCLES OF THE TRACTION MOTORS OF THE ELECTRIC ROLLING STOCK WITH DIFFERENT MODES - Karzova, O. O. (Science and Transport Progress, 2008)
In the article the issues of increase in operation rate of devices of power circuits’ protection for the electric rolling stock are considered, the mathematical model of an engine of consecutive excitation is presented and the results of modeling of transition processes in a start-up mode at different voltage values in the contact mains are given.